Uso da Colagel® na cirurgia da conjuntiva - estudo experimental - Spera, Cláudio Asperti [UNESP]; Schellini, Silvana Artioli [UNESP]; Silva, Maria Rosa Bet De Moraes [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Rahal, Sheila Canavese [UNESP] (Conselho Brasileiro de Oftalmologia, 1998)
The authors studied the ocular tissue reactions produced by the application of the tissue adhesive Colagel® (Cirumédica), with the aim of evaluating the possibility of its accomplishment in the pterigium surgery with the technique of conjunctival transplant. Twelve rabbits were submitted to limbic peritomy with Colagel application on the sclera, being covered by conjunctive. Three animals were not opperated and composed the control group. The animals in the dates 3, 7, 15 and 30 days after surgery were killed. The orbit was exenterated and the material prepared for hystologic exam. Since the first days of postoperative, intense inflammatory reaction was observed in the place of inoculation of the adhesive, as inner the eye. With the evolution, there was an apparent improvement of the inflammation, with limitation of the reaction to the inoculation place; even thought, the intra-ocular inflammation (iritis, vitreitis, coroiditis) continued with necrosis and perforation near the inoculation place. lt can be ended that the Colagel® is not rendered to use in conjunctival surgeries.

Os autores estudaram a reação dos tecidos oculares produzida pela aplicação da cola tecidual Colagel® (Cirumédica), com o intuito de avaliar a possibilidade da sua utilização na cirurgia de exerese do pterígio com a técnica do transplante de conjuntiva. Doze coelhas foram submetidas a peritomia de base límbica com aplicação de Colagel® sobre a esclera que foi recoberta pela conjuntiva. Três coelhas não operadas compuseram o grupo controle. O sacrifício dos animais foi feito 3,7,15 e 30 dias após a cirurgia, procedendo-se a exenteração orbitária e preparo do material para exame histológico. Após a inoculação, observou-se intensa reação inflamatória, tanto no local da inoculação do adesivo, como intra-ocular, com predomínio de células polimorfonucleares. Com a evolução, houve melhora aparente da inflamação, com limitação da reação ao local de inoculação; porém, a inflamação de estruturas intra-oculares (irite, vitreíte, coroidite) continuou, havendo necrose e perfuração ocular próximo ao local da inoculação em alguns animais. Pode-se concluir que a Colagel® não se presta para o uso como adesivo tecidual nas cirurgias da conjuntiva.
Use of Colagel® in conjunctival surgery - experimental study
Keywords: Tissue adhesive; Conjunctival transplant; Pterigium; Adesivo tecidual; Transplante de conjuntiva; Pterígio